Behaviour of RC Frame Structures Under Near-Field Earthquake Loadings - Χαμοσφακίδης, Γεώργιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Στατικής και Αντισεισμικών Ερευνών, 2018)
The purpose of this thesis is to evaluate the seismic behaviour of a 6-storey reinforced concrete structure while tackling the issue of ‘user-friendliness’ of the Open System for Earthquake Engineering Simulation (OpenSees). The latter is accomplished by data extraction from AutoCAD to OpenSees. Several programs, written in language Lisp were developed and presented in the first chapter of the thesis. In subsequent chapters these programs are operated with OpenSees to run a series of nonlinear dynamic analyses to the structure. The excitations are taken from the L’Aquila earthquake, recorded in central Italy in 2009. Specifically, Chapter 1 presents the building structure to be modelled, with plan and elevation views. Following, Lisp routines developed for data extraction purposes from AutoCAD to Tcl are presented in a step-by-step illustrated manner. Chapter 2 deals with the transition from AutoCAD to OpenSees through data extraction and parameters needed to define the OpenSees model in its entirety such as material and load definitions. In Chapter 3 overall results consisting of time-history roof displacements are presented for various recordings of the L’Aquila earthquake. In Chapter 4 the building is strengthened laterally following a concept developed after a powerful earthquake took place in Chile in 1985. It underlines the importance of installing stiff shear walls, lightly reinforced, to a concrete building structure. Chapter 5 provides a rather useful insight to debugging an OpenSees model with Lisp programming. It concentrates, among others, on two frequent sources of error, which are namely connectivity and section definition. Appendix: In the appendix, every program developed for this thesis is presented.